2021
DOI: 10.1038/s12276-021-00560-8
|View full text |Cite
|
Sign up to set email alerts
|

The aftermath of the interplay between the endoplasmic reticulum stress response and redox signaling

Abstract: The endoplasmic reticulum (ER) is an essential organelle of eukaryotic cells. Its main functions include protein synthesis, proper protein folding, protein modification, and the transportation of synthesized proteins. Any perturbations in ER function, such as increased demand for protein folding or the accumulation of unfolded or misfolded proteins in the ER lumen, lead to a stress response called the unfolded protein response (UPR). The primary aim of the UPR is to restore cellular homeostasis; however, it tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(127 citation statements)
references
References 163 publications
2
125
0
Order By: Relevance
“…S5D ). A defective nuclear translocation of sXBP1 has been observed in several pathological conditions such as obesity, insulin resistance, and diabetic nephropathy [ [51] , [52] , [53] ], in which the interaction between sXBP1 and regulatory subunits of PI3K (p85α and p85β) was impaired, aggravating the pathogenesis of diseases [ 4 , 51 ]. Previous studies identified TMBIM6 as a regulator of the pharmacologically-induced ER stress response (particularly p-IRE1α -mediated XBP1 splicing) [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S5D ). A defective nuclear translocation of sXBP1 has been observed in several pathological conditions such as obesity, insulin resistance, and diabetic nephropathy [ [51] , [52] , [53] ], in which the interaction between sXBP1 and regulatory subunits of PI3K (p85α and p85β) was impaired, aggravating the pathogenesis of diseases [ 4 , 51 ]. Previous studies identified TMBIM6 as a regulator of the pharmacologically-induced ER stress response (particularly p-IRE1α -mediated XBP1 splicing) [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, transmembrane ER-resident proteins including inositol requiring enzyme 1α (IRE1α), PKR-like ER kinase (PERK), and activating transcription factor 6α (ATF6α) are activated during UPR activation. UPR is primarily activated to increase adaptive response and restore protein folding, but prolonged ER stress causes adaptive response failure and activates terminal UPR signals promoting cellular apoptosis [ [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UPR is the complex cellular response that is associated with the various membrane biosensors; protein kinase RNA (PKR)-like ER kinase (PERK), inositol requiring enzyme 1α (IRE1α), and activating transcription factor 6 (ATF6) [ 97 ]. Other studies have also indicated that oxidative stress is strongly connected with ER stress [ 108 , 109 ]. Both of them trigger various inflammatory molecules and apoptosis cascades which are involved in the pathogenesis of many diseases, specifically liver injuries.…”
Section: Role Of Oxidative Stress In Endoplasmic Reticulum (Er) Hemostasismentioning
confidence: 99%
“…Heightened ER stress response also results in increased oxidative stress along with autophagy dysfunction [10]. On the other hand, studies also reveal that oxidative stress is considered the major etiology in AD, which contributes to impairment of mitochondrial function [12], ER stress [13], autophagy dysfunction [14], dysfunctional glucose metabolism [15], and an increase in tauopathy and Aβ secretion [12]. Increasing evidence also shows that elevated levels of glycogen synthase kinase 3 (GSK3), a serine/threonine protein kinase, are found in human and mouse models of AD.…”
Section: Introductionmentioning
confidence: 99%